Deteksi Bahan Kimia Obat (BKO) Pada Jamu Sesak Napas Yang Beredar Di e-Marketplace Melalui Kombinasi Metode KLT dan FTIR. - Girvin, Aulia Garnida; Hanwar , Dedi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The circulation of herbal medicines through e-marketplaces raises serious safety concerns due to the illegal addition of chemical drug substances to provide rapid therapeutic effects. This study aimed to detect chemical drug substances, specifically theophylline and chlorpheniramine maleate, in herbal medicines marketed for shortness of breath using a combination of thin-layer chromatography (TLC) and Fourier transform infrared spectroscopy. Qualitative analysis was conducted through optimization and validation of TLC using two mobile phase systems, followed by two-dimensional chromatography to enhance separation selectivity. The optimized systems demonstrated adequate separation with acceptable resolution values. The results showed that all herbal medicine samples had retention factor (Rf) values comparable to the standard. FTIR confirmation showed typical absorption bands of chlorpheniramine maleate (CTM) and theophylline, so that all samples (5 of 5) were declared positive for containing chemical drugs, with CTM identified in samples 1 and 4 and theophylline in samples 2, 3, and 5. These findings indicate that some herbal medicines circulating in e-marketplaces contain chemical drugs, which are not in accordance with the provisions of traditional medicine regulations.